1037 Prevalence of Obstructive Sleep Apnea in Intracerebral Hemorrhage, A Retrospective Study. (27th April 2018) - Fournier, L; Tallavajhula, S; Okpala, M; Vahidy, F; Sharrief, A
Abstract: Introduction: Obstructive sleep apnea (OSA) is a risk factor for stroke recurrence and is present in up to 70% of ischemic stroke (IS) survivors. Available data suggest that OSA is not as common in intracerebral hemorrhage (ICH). OSA has been more extensively studied in IS compared to ICH despite higher risk of uncontrolled hypertension, stroke recurrence and stroke mortality in the latter. Furthermore, screening for sleep apnea is suggested after IS or transient ischemic attack (TIA), but not for ICH. We sought to determine whether patients with ICH were as likely to have OSA as compared to IS patients, and to identify differences between indices of OSA between these two groups. Furthermore, we sought to determine whether hospital variables predicted OSA. Methods: We identified patients with IS, TIA or ICH referred for polysomnography (PSG) from 01/2013 - 07/2017. Demographic and clinical data were abstracted from medical records. We used t-test, chi squared and Fisher's exact test as appropriate for univariate analysis and multiple logistic regression for multivariate analysis. Results: We identified 82 patients (68% IS, 21% ICH, 11% TIA), of whom 58 (71%) had OSA. Median time from stroke to sleep study was 119 days (IQR 62–244). There was no significant difference between IS/TIA and ICH in OSA prevalence. Only higher Body Mass Index (BMI) was associated with presence of OSA (p<0.01). Comparing IS/TIA and ICH patients with OSA, there was no difference in mean Apnea Hypopnea Index (AHI) or REM AHI. Among 67 patients with hospital data, there was a suggestion that ICH patients with OSA were more likely to have a night-time BP spike (vs daytime) compared to IS/TIA patients (36% vs 13%, p=0.08). Conclusion: In our study, patients with ICH had similar prevalence of OSA compared to IS/TIA patients. Further studies are needed to evaluate predictors of OSA in ICH and the impact of OSA on ICH morbidity and mortality. Our findings suggest that ICH patients should be referred for PSG. Support (If Any): None.